PENGARUH PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI DI WILAYAH GERBANGKERTOSUSILA TAHUN 2019-2023 - Deftian Fitra Pradana; Risqi Noor Hidayati Putri (Jurnal Ekonomika : INDEPENDEN, 2025)
This study aims to examine how Regional Original Income (PAD) affects economic growth in the Gerbangkertosusila region between 2019 and 2023, which consists of four main components: Regional Taxes, Regional Levies, Results from the Management of Separated Regional Assets, and Other Legitimate PAD. This study uses a quantitative approach with a panel data regression method using the Fixed Effect Model (FEM). The test results indicate that partially, Regional Taxes have a positive and significant effect on economic growth. Meanwhile, Regional Levies, Results from the Management of Separated Regional Assets, and Other Legitimate PAD have no significant effect on economic growth. Simultaneously, all four components of PAD have a significant effect on economic growth in the Gerbangkertosusila region. This finding demonstrates the importance of optimizing PAD, especially components that are proven to be able to drive economic growth, as a basis for regional fiscal policy making.